Corn response to incremental applications of sulfate‐sulfur. (1st July 2021) - Goyal, Diksha; Franzen, David W.; Cihacek, Larry Joseph; Chatterjee, Amitava
Abstract: Reports of sulfur (S) deficiency symptoms in corn ( Zea mays L.) fields of the Red River Valley of North Dakota and Minnesota are increasing. Current soil tests cannot predict the availability of S correctly due to the presence of gypsum in soils of this region. Field trials were conducted to determine corn yield and S uptake response to incremental applications of S (0, 11, 22, 33, and 44 kg S ha –1 ) in the form of ammonium sulfate [(NH4 )2 SO4 ]. Corn yield and S uptake varied significantly between sites. Out of 12 sites, only two sites had the highest corn yield without S application. Corn grain S removal ranged between 11 and 17 kg S ha –1 at harvest. Fertilizer‐S (SO4 ) application did not result in a significant yield response. The current recommendation of 11 kg S ha –1 may be necessary to reduce the risk of future S deficiency across this region and compensate for the removal of S in grain due to the uncertainty of adequate plant available S. Core Ideas: Corn grain yield and S uptake did not respond to a fertilizer‐S application rate. Sulfur mineralization was enough to fulfill crop S demands. Soil organic matter content was not a reliable predictor for corn S response.